Integrating Generative AI and Intelligent Agents for Enhanced Data Security in Healthcare Analytics - Viswanatha Raju Sangaraju (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Generative AI and Intelligent Agents: A New Paradigm for Improved Data Security in Healthcare Analytics As healthcare data is exponentially increasing, protecting sensitive information while enabling capable data analysis and processing has become critical. This research investigates the synergistic integration of Generative AI—renowned for its prowess in generating synthetic data and detecting anomalies—and Intelligent Agents, capable of smart and autonomous decision-making processes, to establish a dynamic, adaptive approach to data protection in healthcare environments. Digital signature, secured file transfer protocol, firewalls, and Intrusion Detection System (IDS) can be implemented to materials for products to enhance data security, which can be maintained through an integrated system that uses advanced encryption, real-time monitoring, and predictive models to cut down on vulnerabilities, blockage of unwanted access, and secure data exchanges. This paper adds value by suggesting an ideal framework for every healthcare analytics platform to ensure ethics, compliance, trust, and scalability in order to balance patient privacy and corporate gain.